Photocatalytic degradation of palm oil mill secondary effluent - Hayati Hairom, Nur Hanis; Abd Hadi, Nurul ‘Aisyah; Ismail, Nurul Hana; Zainuri, Nur Zarifah; Abu Bakar Sidik, Dilaelyana; Desa, Amira Liyana; Misdan, Nurasyikin; Yusof, Norhaniza; Mohammad, Abdul Wahab (Penerbit Uthm, 2018)
Palm oil industry is one of the industries that has major disposal problem in disposing the lignocelluloic biomass such as oil palm trunks (OPT), oil palm fronds (OPF), empty fruits bunches (EFB) and palm pressed fibres (PPF), palm shells and palm oil mill effluent (POME) [1]. Amongst all waste produced, POME is the most difficult waste to treat due to its high volume generated [2]. POME consists of 95-96% water, 0.6-0.7% of oil and 4-5% and total solid. Although it was said that POME is nontoxic, however the abundance of POME in water stream could lead to oxygen depletion in water stream as POME contains high amount of nitrogen (N), phosphorous (P), potassium (K), magnesium (Mg), and calcium (Ca) which later on could lead to plant growth in aquatic region. POME also consists of sterilizer condensate, separator sludge and hydrocyclone (DOE 1999). The treatment of POME generally undergo ponding system, open tank digester and extended aeration system, or closed anaerobic digester and land application system. Palm oil mill secondary effluent (POMSE) is the result of treatment of POME and is characterized by having a thick, brownish color and bad odor wastewater. Although POME was claimed to be treated with one of the systems, several studies showed that the POMSE still exceed the standard discharge limit set by both Department of Environment (DOE) Malaysia and Environment Quality Act (EQA) 1974